SARS-CoV-2 and the Gastrointestinal Tract in Children - Puoti, Maria Giovanna; Rybak, Anna; Kiparissi, Fevronia; Gaynor, Edward; Borrelli, Osvaldo (Frontiers in Pediatrics, 2021)
Coronavirus disease 2019 (COVID-19), caused by acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is predominantly a respiratory disease. Howerer, its significant impact on the gastrointestinal (GI) system is now clear. SARS-CoV-2 enters cells via the angiotensin-converting enzyme-2 (ACE-2) receptor, which is abundantly expressed in lung cells, but also in enterocytes. Several etiopathogenetic mechanisms have been suggested to explain the GI involvement in COVID-19, including loss in intestinal absorption, microscopic mucosal inflammation and impaired ACE-2 function, which plays a significant role in maintaining gut homeostasis. In children, COVID-19 associated GI symptoms are more common than in adults, with infants more likely to be affected. The GI manifestations include anorexia, nausea, vomiting, diarrhoea and abdominal pain, which may represent the earliest presenting symptoms of the disease. However, although rare, a significant GI mucosal inflammation, such as terminal ileitis mimicking an atypical appendicitis, has been reported also in the acute phase. COVID-19 pandemic has posed a significant challenge in healthcare provision in term of ability in providing safe diagnostic endoscopic procedures, face-to-face consultations and offering comprehensive care. For instance, changes in health services have raised the risk of empirical or sub-optimal management of inflammatory bowel disease (IBD) due to delayed endoscopic assessment. In functional GI disorders (FGIDs), the impact has been seen through disruption of routine, lack of social contacts, unfamiliar distance learning and financial insecurity. This review will discuss the acute GI involvement in COVID-19 in children and reflect on challenges and major changes observed in clinical practice during COVID-19 pandemic, by sharing both, the published literature and personal experience. We will also suggest potential strategies for providing optimal gastroenterology care during this unprecedented era.